Minat Dan Motivasi Belajar Bahasa Jepang (Studi Kasus Terhadap Mahasiswa Jurusan Sastra Indonesia 2016/2017 FIB Undip) - Yuliani Rahmah (KIRYOKU, 2019)
(Title: Interest and Motivations in Japanese Learning) This article is the result of a case study for Japanese learners as the second foreign language. The large number of students taking Japanese language courses is the basis for this qualitative research. The respondent in this research was 70 Indonesian Literature students in 2016/2017. The purpose of this study research was to determine the interests and motivations of their interest in learning Japanese. There are four elements of interest and two types of motivation that are the focus of this research. With the questionnaire and interview methods, as a result it is known that the interest of the respondents is quite high based on the element of pleasure as the most answer. This element of pleasure includes the respondents' interest in  the Japanese things such as anime,manga and festivals. In terms of motivation, it is indicated that the most of the respondent reason refers to type of integrative motivation. The emergence of that integrative motivation is based on their interest in the uniqueness of Japanese language  and the attractiveness of Japanese cultural arts.